The Nature of Thule Eskimo Whale Use - McCartney, Allen P. (ARCTIC, 1980)
Archaeologists for the past half century have considered bowhead whaling to be an important and integral part of Thule Eskimo subsistence. This position has come into question recently. Arguments are set forth favoring the predominant archaeological view that bowheads were hunted and extensively used during the period A.D. 1000-1300 in much of the Canadian Arctic. Direct, indirect, and circumstantial evidence is outlined, ranging from the presence of whaling gear and graphic whaling depictions to arguments of resource maximization and ample storage capacity at Thule winter sites. Differences in interpreting the Thule record appear to reflect different methodological approaches of ethnologists and archaeologists.